Analyzing social representations from the theory of the central core: A qualitative methodological proposal - Díaz-Herrera, Claudio; Olivares Peña, Karen; Martínez Matamala, Carlos; Muñoz-Figueroa, Pilar (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
Social representations can be conveyed through language, which expresses a construction of the reality. Assuming the complex task of analyzing the results of a qualitative study, this article exposes from a structuralist approach, a proposal to analyze and construct social representations from the central core theory. Thus validate in methodological terms, a way to graphically express results for a holistic analysis and interpretation of these central and peripheral notions. The proposal is elaborated for application in studies with primary sources such as interviews and their treatment through a content analysis.